2012
DOI: 10.1017/s1092852912000508
|View full text |Cite
|
Sign up to set email alerts
|

High-dose desvenlafaxine in outpatients with major depressive disorder

Abstract: The mean daily desvenlafaxine dose range over the duration of the trial was 267-356 mg (after titration). The most frequent TEAEs in the safety population (n = 104) were nausea (52%) and headache (41%), dizziness (31%), insomnia (29%), and dry mouth (27%). All TEAEs were mild or moderate in severity. Thirty-four (33%) patients discontinued from the study because of TEAEs; nausea (12%) and dizziness (9%) were the most frequently cited reasons. The mean change in HAM-D(17) total score for the intent-to-treat pop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 20 publications
(42 reference statements)
0
6
0
Order By: Relevance
“…The evidence base for the treatment of mood disorders, and disorders in general, is usually derived from efficacy trials rather than effectiveness trials, and therefore their applicability to routine psychiatric practice is limited. Many survey respondents indicated using medications at higher than usual doses—a practice which, with careful monitoring, is supported by the evidence‐based literature on treatment resistant mood disorders (e.g., see ). A further strength of the survey is that it provided insights about practitioner decisions in a number of common and important clinical situations that require the thoughtful application of evidence‐based knowledge.…”
Section: Discussionmentioning
confidence: 94%
“…The evidence base for the treatment of mood disorders, and disorders in general, is usually derived from efficacy trials rather than effectiveness trials, and therefore their applicability to routine psychiatric practice is limited. Many survey respondents indicated using medications at higher than usual doses—a practice which, with careful monitoring, is supported by the evidence‐based literature on treatment resistant mood disorders (e.g., see ). A further strength of the survey is that it provided insights about practitioner decisions in a number of common and important clinical situations that require the thoughtful application of evidence‐based knowledge.…”
Section: Discussionmentioning
confidence: 94%
“…The incidence of taper/poststudy-emergent adverse events after the discontinuation of desvenlafaxine at 200-400 mg/day ranged from 42 to 52% [44,45]. In both studies the most common discontinuation symptoms were dizziness, nausea, and headache.…”
Section: Withdrawal Symptoms In Open Trials and Naturalistic Prospectmentioning
confidence: 93%
“…Eight open-label reports evaluated the efficacy and tolerability of venlafaxine [38,39], duloxetine [40][41][42], levomilnacipran [43], and desvenlafaxine [44,45] (online suppl. Table 3).…”
Section: Withdrawal Symptoms In Open Trials and Naturalistic Prospectmentioning
confidence: 99%
“…In a clinical study, DVS at high doses of 200-400 mg daily were shown to be effective and safe and DVS is currently rated safe for up to 400 mg a day. 26,27 In a previous canine study, DVS at one single dose of 50 mg reduced the percentage of normal slow waves, decreased gastric tone, and inhibited antral contractions in the postprandial state. 14 In the current study, one single dose of DVS at 50 or 100 mg was found to delay gastric emptying of solid in dogs.…”
Section: Discussionmentioning
confidence: 90%
“…So we aimed to further explore the effects of DVS at high doses on GI motility in dog for the safety in patients. In a clinical study, DVS at high doses of 200–400 mg daily were shown to be effective and safe and DVS is currently rated safe for up to 400 mg a day …”
Section: Discussionmentioning
confidence: 99%